Perkembangan Pasar Aur Kuning Kota Bukittinggi Tahun 1981-2017 - Sigit Prasetyo; Etmi Hardi (Galanggang Sejarah, 2023)
This research examines the development and background of the emergence of the Aur Kuning Market in Bukittinggi City in 1981-2017. The emergence of this market is due to the density of traders in the Upper Market, which makes traders interested in moving to the Aur Kuning Market. Along with the development of the Aur Kuning Market and supporting facilities accompanied by low price conditions, Aur Kuning Market has become a textile wholesale center in West Sumatra and even on Sumatra Island, so that its existence has become part of the economic center of the City of Bukittinggi. The problems raised in this study are how the development of the Aur Kuning Market in 1981-2017 and what was the background for the establishment of the Aur Kuning Market in 1981-2017. The purpose of this study is to describe the background of the establishment of Pasar Aur Kuning in 1981- 2017. Then the development of the Aur Kuning Market in 1981-2017. This research is included in qualitative research using historical methods in the form of library studies, archives and interviews. Based on the results of this study, it can be concluded that the background to the emergence of the Aur Kuning Market in 1981 was due to the Presidential Instruction in 1975 through SK Permendagri No. 15 of 1975. Some of the land used for this terminal and market is owned by the community and the government, namely land inherited from Japan.